Evaluation Of Sanitation And Suitable Drinking Water Achievements And Implications For Regional Development Policies In Central Sulawesi Province - Triasih Amanda (Universitas Muhammadiyah Palu, 2026)
Access to adequate sanitation and drinking water is a fundamental human right that remains challenging in many regions of Indonesia, including Central Sulawesi Province. This study aims to evaluate the achievement of adequate sanitation and drinking water services and formulate appropriate policy recommendations to address access disparities, particularly related to poverty. The research employs a quantitative descriptive approach, using secondary data from the Central Statistics Agency (2019–2024), and a qualitative approach using the USG (Urgency, Seriousness, Growth) method and policy alternative evaluation based on the Bardach framework (2012). The results indicate that adequate sanitation access increased from 72.5% (2019) to 80.1% (2023), and adequate drinking water access from 82.0% to 87.8%. However, the nexus between poverty and access to basic services emerged as the primary problem with the highest USG score (14). An evaluation of five policy alternatives shows that the whole-of-government approach achieved the highest score (18/20), followed by the infrastructure-based (13), community-based (15), social protection (17), and place-based (16) approaches. The conclusion is that an integrated cross-sectoral policy is most effective in breaking the poverty trap chain and improving sustainable access to sanitation and drinking water. The main recommendation is the issuance of a Governor's Regulation on the Cross-Sectoral Integration Framework in Central Sulawesi Province.